Dalgliesh. Series 2 [videorecording (DVD)] - Edmundson, Helen, 1964- (RLJ Entertainment, 2023)
In 1970s England, Dalgliesh and his junior, DS Kate Miskin, investigate the murders of a forensic scientist, a controversial lawyer, and a young doctor at odds with his family.